Influence of Problem Solving Learning Model on Motivation of Learning Scince In Class IV SD Negeri Sukamakmur 1 - Yulistina Nur DS; Dina Vera Yuni; Harmawati - (LPPM Universitas Buana Perjungan Karawang, 2020)
This study aims to determine the effect of model problem solving with students learning motivation in scince subjectts at SD Sukamakmur 1, TelukJambe Timur district. This research is a quantitative research. The population used in this study were all grade IV studenta of SD Negeri Sukamakmur 1, TelukJambe Timur subdistrict, amounting 80 students. Data collection technique to test the hypothesis is done by calculating the product moment statistics.The results of the validity of the students’ learning motivation questionnaire in natural science subject obtained 27, which were declared valid from 40 items tested. The reability test results an rn value 3,470. Hypothesis testing results, there are significant differences between students’ learning motivation in science subjects with student learning outcomes. It was obtained 84,48 tables in 2,024 with a significance of 0,05 and n=40 indicating that the hypothesis was accepted. From the results of this study it can be concluded that the learning motivation of students in science subjects with learning outcomes has an influence.